2022
DOI: 10.1021/acs.inorgchem.2c03200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfide Perovskites by Sulfurization with Boron Sulfides

Abstract: Chalcogenide perovskites (CPs), with the general composition ABX3, where A and B are metals and X = S and Se, have recently emerged as promising materials for application in photovoltaics. However, the development of CPs and their applications has been hindered by the limitations of available preparation methods. Here we present a new approach for the synthesis of CPs, based on the sulfurization of ternary and binary oxides or carbonates with in situ formed boron sulfides. In contrast to the previously describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Recent studies have also demonstrated that lowertemperature reactions involving the use of sulfurization agents, e.g., boron sulfides or elemental sulfur, can also be effective in reactions with ternary oxides or other precursors. 18,19 Beyond the perovskite-type chalcogenides, recent investigations have shown that group-IV chalcogenides forming in alternative structures can possess similar favorable optoelectronic properties. In metal selenides where the perovskite-type structure has yet to be obtained, synthetic attempts have instead yielded the Ba 8 M 2 Se 11 (Se 2 ) (M = Zr, Hf) and Ba 9 Hf 3 Se 14 (Se 2 ) structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also demonstrated that lowertemperature reactions involving the use of sulfurization agents, e.g., boron sulfides or elemental sulfur, can also be effective in reactions with ternary oxides or other precursors. 18,19 Beyond the perovskite-type chalcogenides, recent investigations have shown that group-IV chalcogenides forming in alternative structures can possess similar favorable optoelectronic properties. In metal selenides where the perovskite-type structure has yet to be obtained, synthetic attempts have instead yielded the Ba 8 M 2 Se 11 (Se 2 ) (M = Zr, Hf) and Ba 9 Hf 3 Se 14 (Se 2 ) structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several new methods for the preparation of CPs under more moderate conditions have been reported. 15,16 Computational predictions also played a substantial role in the increased interest in developing CP materials. Recently, the density functional theory (DFT)-based high-throughput computational screening of varied compositions was performed to identify compounds that are thermodynamically stable and have electronic properties suitable for exploitation in photovoltaics and optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the toxicity of one of its key components, Pb, and the limited thermal and chemical stability of halide perovskites represent major challenges to their effective application. , Chalcogenide perovskites (CPs) have recently been recognized as a possible alternative with a similar electronic structure, better thermal and chemical stability compared to their halide counterparts, and generally lower toxicity. Although chemical methods for the preparation of CPs are known for more than 60 years, the development of practical applications of CPs has been slow because of the high temperatures and long reaction times required. Recently, several new methods for the preparation of CPs under more moderate conditions have been reported. , …”
Section: Introductionmentioning
confidence: 99%
“…Especially, their applicability in solar cell applications is still unknown. Further, since both oxides and many of the respective sulfides (the extreme ends of this series) based perovskites have now been well studied, [22][23][24][25] it becomes even more important to understand the nature of oxysulfides with varying concentration of oxygen and sulfur, specifically when the compound is sulfur-rich, owing to the stability of sulfur-rich compounds. [26,27] It may thus be expected that the sulfur-rich oxysulfide perovskites may provide an optimal bandgap and a suitable stabilty that is being desired for the nextgeneration water-splitting devices.…”
Section: Introductionmentioning
confidence: 99%